Penjualan berbasis digital dan literasi digital terhadap peningkatan profitabilitas UMKM di Kecamatan Malalayang Kota Manado - Manuho, Jessica Jeniver; Pontoh, Winston; Kapojos, Peter M. (Riset Akuntansi dan Manajemen Pragmatis, 2025)
This study investigates the effect of digital-based sales and digital literacy on the profitability of Micro, Small, and Medium Enterprises (MSMEs) in Malalayang District, Manado City. Recognizing the growing importance of digital transformation, the research examines how adopting digital sales platforms and enhancing digital literacy contribute to improving business performance. A quantitative approach was employed using primary data collected from 50 MSME owners through structured questionnaires. Multiple linear regression analysis with Jamovi v2.3.28 was used to test the hypotheses after conducting validity, reliability, and classical assumption tests. The findings reveal that both digital-based sales and digital literacy individually and jointly have a significant and positive effect on MSME profitability. These results highlight the critical role of digital competencies and online marketing strategies in enhancing the financial performance of MSMEs. The study contributes to the literature by providing empirical evidence from a developing region and offers practical implications for policymakers and entrepreneurs in designing effective digital empowerment programs for MSMEs.